Interface stress control mechanism of engineering plastic gaskets during the low-amplitude and long-pulse-width dynamic loading process - Xu, Feng; Jiang, Jianwei; Men, Jianbin; Wang, Shuyou; Li, Mei (Frontiers in Materials, 2025)
Impact and protection are hot topics of concern in modern military and civilian fields. However, existing research focuses more on high-speed, high-frequency impact, explosion, and other loading conditions, while studies on the protective mechanisms and stress-deformation processes of materials during long-pulse-width and low-amplitude dynamic impact processes are relatively limited. This work investigates the interfacial stress control mechanism of engineering plastic gaskets on protected components under long-pulse-width loading, and employs the finite element method (FEM) to simulate the impact protection processes of gaskets with different material parameters. The influence of gasket material parameters on the interface protection effects for protected vulnerable components was obtained, and the relevant protective mechanisms were revealed. The surface fitting method was used to optimize the performance parameters of protective materials, and the impact protection effect of optimized gaskets under simulated launch loading was verified through large-scale drop hammer tests. Key findings include: (1) Under long-pulse, low-amplitude dynamic loading, the Von Mises stress distribution on impact surfaces of vulnerable components correlates with the anisotropic deformation capacity of protective materials; (2) Controlling the variation and coupling of triaxial stresses at the interface between protective materials and vulnerable components is critical for achieving protection; (3) Engineering plastic protective materials with moderate de-formation capabilities demonstrate superior effects in improving interface stress distribution of typical composite vulnerable components. The research outcomes provide important references for impact protection design under long-pulse dynamic loading process.